Changes in intraocular pressure after cataract surgery: Analysis of the Swedish National Cataract Register Data. Issue 8 (August 2015) - Zetterström, Charlotta; Behndig, Anders; Kugelberg, Maria; Montan, Per; Lundström, Mats
Abstract : Purpose : To analyze changes in intraocular pressure (IOP) after cataract surgery based on data from the Swedish National Cataract Register (NCR). Setting : Ophthalmic surgery units in Sweden. Design : Prospective database study. Methods : Data for 2012 through 2014 were obtained prospectively from the NCR. The outcome register of the NCR has collected data on IOP before and a mean of 37.7 days ± 29.1 (SD) after cataract surgery since 2012. Results : The analyses were based on 20 437 cataract extractions reported during 1 month each year to the outcome registry of the NCR. Cataract surgery was found to reduce IOP by a mean of 1.46 mm Hg, which was statistically significant ( P < .001). A larger IOP reduction was seen in cases with a higher preoperative IOP ( r = 0.557, P < .001). Older patients and shorter eyes had a greater IOP reduction after surgery ( P < .001 and P = .001, respectively). Women had a greater IOP reduction than men ( P = .04) When high IOP was given as an indication for surgery, the IOP reduction after cataract surgery was 5.50 mm Hg compared with a reduction of 1.40 mm Hg in patients for whom this indication was not given ( P < .001). Patients with glaucoma or pseudoexfoliation (PXF) had a more pronounced IOP reduction than patients without these diagnoses ( P < .001). Conclusion : Cataract surgery had an IOP‐lowering effect, in particular in older patients, women, short eyes, eyes with high preoperative IOP, and eyes with glaucoma or PXF. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.